2003
DOI: 10.1096/fj.03-0515fje
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein 3 as a mitochondrial fatty acid anion exporter

Abstract: In contrast to UCP1, the primary function of UCP3 is not the dissipation of energy. Rather, several lines of evidence suggest that UCP3 is related to cellular long-chain fatty acid homeostasis. If long-chain fatty acids enter the mitochondrial matrix in their non-esterified form, they cannot be metabolized and may exert deleterious effects. To test the feasibility that UCP3 exports fatty acid anions, we systematically interfered at distinct steps in the fatty acid metabolism pathway, thereby creating condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 41 publications
8
96
2
5
Order By: Relevance
“…Thus, the role of UCP3 would be to protect muscle tissue against lipotoxicity, rather than to regulate energy expenditure. Schrauwen et al [42] have suggested There was a significant and independent relationship of BMI (p= 0.002) and MFN2 (p=0.006) with insulin sensitivity measured in morbidly obese women before and during RYGB-induced weight loss that UCP3 could contribute to outward translocation of NEFA, occurring when NEFA availability exceeds mitochondrial oxidative capacity. This mechanism would protect the mitochondria from NEFA accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of UCP3 would be to protect muscle tissue against lipotoxicity, rather than to regulate energy expenditure. Schrauwen et al [42] have suggested There was a significant and independent relationship of BMI (p= 0.002) and MFN2 (p=0.006) with insulin sensitivity measured in morbidly obese women before and during RYGB-induced weight loss that UCP3 could contribute to outward translocation of NEFA, occurring when NEFA availability exceeds mitochondrial oxidative capacity. This mechanism would protect the mitochondria from NEFA accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, one wonders about the validity of rejecting carrier function solely on the basis of amino-acid identity to the carnitine carrier. A number of biochemical models have in fact been proposed in which these UCP1-homologues would operate as fatty-acid carriers across the mitochondria, and the putative function of UCP2 and/or UCP3 would be to export fatty acids out of the mitochondria when fatty acid supply or oxidation predominates, such as in the skeletal muscle during fasting and high-fat feeding [77][78][79]). Most of the proposed models have focused on UCP3, primarily because of the inability to detect UCP2 protein in organs/tissues known to be important sites of fat metabolism (skeletal muscle, heart, brown adipose tissue).…”
Section: Ucp1-homologues: a Link With Regulation Of Lipids As Fuel Sumentioning
confidence: 99%
“…In other models, UCP2 and/or UCP3 are postulated to be involved in the translocation of the fatty acid anions from the matrix side to the cytosolic side of the mitochondrial membrane [42,71,79]. The fatty acid anions would be protonated, and the UCP1-homologues would then dflipflopT these neutral fatty acids back to the matrix side [70,71,79], resulting in a lowering of the proton gradient and hence increased heat production.…”
Section: Ucp1-homologues: a Link With Regulation Of Lipids As Fuel Sumentioning
confidence: 99%
See 1 more Smart Citation
“…3 It has been also proposed that UCP3 could behave as a mitochondrial fatty acid anion transporter thereby mitigating lipotoxicity. 4 Overall, the metabolic modifications associated with UCP3 expression and more particularly muscle energy consumption and fat metabolism warrant further investigations.…”
Section: Introductionmentioning
confidence: 99%